Understanding root caries risk in Indonesian adults: evidence from a nationwide survey - Yuanita Lely Rachmawati; Agustine Hanafi Putri; Ninuk Hariyani; Melissa Adiatman; Ollie Yiru Yu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Root caries (RC) remains a global burden and is often found in older adults. Risk factors for RC can vary in different countries. Purpose: This study aimed to determine the prevalence and risk factors of RC in Indonesian adults. Methods: This study analyzed data from Indonesia’s 2018 National Health Survey, which included 37,057 respondents aged ≥15 years. The survey collected data on sociodemography, oral health practices, general health behaviors, and oral conditions. An oral examination was conducted to measure the number of teeth with RC, decayed, missing, or filled teeth, as well as bleeding on probing (BOP), attachment loss, pocket depth, and number of eroded teeth. Logistic regression was generated to estimate odds ratios and confidence intervals. Results: The prevalence of RC was 59.4%, mainly occurring in participants aged >45 years. Those aged >60 years had 2.52 times (adjusted odds ratio [AOR] = 2.52; 95% confidence interval [95%CI], 2.26–279) the number of RC compared with those who were younger. The likelihood of RC was increased by having a lower education (1.47 times; AOR = 1.47; 95%CI, 1.28–1.70) and never visiting a dentist (1.64 times; AOR = 1.64; 95%CI, 1.22–2.19). Decayed, missing, or filled teeth were shown to increase the risk of RC, where more coronal caries indicated a higher risk. Those with BOP (+) and attachment loss of >3 mm had a greater risk of developing RC. Conclusion: The prevalence of RC was relatively high, occurring mainly in middle-aged and older adults. Root caries in the Indonesian adult population reflects a complex interplay of multiple contributing factors, including sociodemography, oral health practices, general health behaviors, and oral conditions.